2022
DOI: 10.2478/raon-2022-0011
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hypofractionated helical tomotherapy for older patients with localized prostate cancer: long-term outcomes of a phase I–II trial

Abstract: Background Our previous study showed that two different regimens of moderate hypofractionated radiotherapy (HFRT) delivered with helical tomotherapy (HT) are well tolerated in older prostate cancer patients. We provide a longterm efficacy and toxicity after > 7 years of follow-up. Patients and methods The study recruited 33 patients from February 2009 to July 2011 (76 Gy/34F; Group-1); and 34 from July 2011 to February 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…The authors recently reported the long-term outcomes of their analysis where, after a median follow-up of 8.9 years, the 7y PFS was 71.6% and the 7y-biochemical-free survival, prostate cancer specific survival, and OS for all the patients were 77.6%, 91.9%, and 77.0%, respectively. Moreover, they reported a 7y G ≥2 late GU toxicities 6.2% and 6.3% in Group-1 (normal fraction action) and -2 (hypofractionation group), respectively (35).…”
Section: Discussionmentioning
confidence: 97%
“…The authors recently reported the long-term outcomes of their analysis where, after a median follow-up of 8.9 years, the 7y PFS was 71.6% and the 7y-biochemical-free survival, prostate cancer specific survival, and OS for all the patients were 77.6%, 91.9%, and 77.0%, respectively. Moreover, they reported a 7y G ≥2 late GU toxicities 6.2% and 6.3% in Group-1 (normal fraction action) and -2 (hypofractionation group), respectively (35).…”
Section: Discussionmentioning
confidence: 97%